PENGARUH PROFITABILITAS, RESIKO KEUANGAN, UKURAN PERUSAHAAN, GROWTH, STRUKTUR KEPEMILIKAN MANAJERIAL DAN DIVIDEND PAYOUT RATIO TERHADAP MANAJEMEN LABA PADA PERUSAHAAN SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - MUHAMMADINAH MUHAMMADINAH MUHAMMADINAH (I-Finance Journal, 2016)
This study aims to identify and analyze the effect of profitability, financial risk, company size, company growth (Growth), managerial ownership structure and dividend payout ratio simultaneously on earnings management in the banking sector companies listed on the Indonesian Stock Exchange (BEI). The population used in this study are all companies that go public banking sector listed on the Indonesia Stock Exchange that as many as 40 Bank. The process of determining the sample in this study using purposive sampling with criteria established in order to obtain 8 banking company. The analysis technique used is quantitative method with multiple regression. Based on the results of the study showed that variables simultaneously Profitability, Financial Risk, company size, Growth, Managerial Ownership Structure, Dividend Payout Ratio has no effect on Earnings Management while partial only and Growth Credit Risk variables that significantly influence Earnings Management.Keywords: Profitability, Financial Risk, company size, Growth, Managerial Ownership Structure, Dividend Payout Ratio and Earnings Management